PLANT INVENTORY OF CAMPUS AREA AT UNIVERSITAS SYIAH KUALA, BANDA ACEH - Puspa, Vivera Ruselli; Djufri, Djufri; Hartini, Suji; Rusdi, Muhammad (Universitas Islam Negeri Ar-Raniry, 2022)
Syiah Kuala University is one of the public universities in Banda Aceh, where each office unit has an Open Green Space (OGS). The green space is planted by plants, both intentionally and wildly. There are several plant habitus, including herbs, shrubs, and trees. There is no information on the list of flora species on the campus of Syiah Kuala University. Therefore, it is necessary to carry out an inventory of plant species in the campus area has been carried out. The study was conducted using a survey method at 21 observation sites. The survey results show that there are 130 species from 41 families. Species with the highest number of species were Poaceae, Asteraceae, and Arecaceae. The most common habitats found were trees (50.77%), herbs (28.46%), shrubs (16.92%), and bush (3.86%). The species are trees intentionally planted for the open green space to function as a shade or shelter.